14 What are the opportunities for cancer care and related research in primary care? A qualitative study of the views of patients, carers and practice staff. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Clark, Joseph; Amoakwa, Elvis; Blenkinsopp, John; Reedy, Florence; Johnson, Miriam
Abstract : Background: Research to identify the role of primary care in cancer care is important. However, trials in primary care are difficult. Aims: To understand how patients, families and primary care clinicians view their role in cancer care and opportunities for cancer primary care research. Methods: Qualitative study embedded within a feasibility cluster randomised controlled trial of a primary care based needs assessment intervention. The Supportive Cancer Needs Survey (SCNS) was the main outcome. In-depth interviews with trial participants (patients, carers) and focus groups with primary care staff explored views on cancer care in primary care and experiences of participation in the trial. Data were recorded, transcribed verbatim and analysed thematically by three independent researchers. Results: We interviewed 15 cancer patients, 3 carers and conducted 4 focus groups (n=11). Three themes were generated: (1) Satisfaction with current care, (2) Key time-points for improved cancer care, (3) Information and research. Satisfaction with current care amongst patients was high in spite of reported high levels of unmet needs on the SCNS indicating low expectation. Most patients undergoing cancer treatment were unsure when they should access primary care. Patients and carers highly valued proactive contact from their practice following diagnosis although this was perceived as unusual. Post-oncology discharge was a key time-point for information needs and support by patients and clinicians. Patients were reluctant to consider palliative care in spite of palliative care needs – indicating low understanding. Some felt therapeutic benefit from completing study measures. In spite of positive attitudes to cancer research by consented participants, some had poor understanding of study procedures. Conclusion: Patients are satisfied with cancer primary care despite unmet needs. Palliative care is poorly understood by many who may benefit. Research participation may benefit some patients.